Expansion of an ancient lake in the Kathmandu basin of Nepal during the Late Pleistocene evidenced by lacustrine sediment underlying piedmont slope - Saijo, Kiyoshi; Kimura, Kazuo (Himalayan Journal of Sciences, 2008)
We investigated the geomorphology and surface geology of the piedmont slope on the margins of the Kathmandu basin in the Nepal Himalaya in order to establish Late Pleistocene geography and especially the extent of the ancient lake in the basin. The piedmont slope consists of detrital deposits of colluvial or fluvial origin, underlain and interfingered by organic muddy sediments with radiocarbon ages of about 30,000 yr BP. Detritus from the surrounding hillslopes and lacustrine sediments were alternately deposited as the lake level rose at about that time. The ancient lake in the Kathmandu basin thus reached a level of between 1400 and 1440 m at around 30,000 yr BP, when it covered almost the entire basin. Because the cols on the surrounding divide are higher than this estimated lake level, and because reddish soils and weathered bedrock are observed on these cols, we conclude that overflow from an outlet other than the Bagmati River probably did not occur. Drainage of the ancient lake by the Bagmati River began just after 30,000 yr BP. Key words: Nepal, Kathmandu basin, piedmont slope, lacustrine, lake level change, Late Pleistocene Himalayan Journal of Sciences Vol.4(6) 2007 p.41-48